Shrub-mediated effects on soil nitrogen determines shrub-herbaceous interactions in drylands of the Tibetan Plateau - Cui, Guangshuai; Pugnaire, Francisco I.; Yang, Liu; Zhao, Wanglin; Ale, Rita; Shen, Wei; Luo, Tianxiang; Liang, Eryuan; Zhang, Lin (Frontiers in Plant Science, 2023)
Shrub promotes the survival, growth and reproduction of understory species by buffering the environmental extremes and improving limited resources (i.e. facilitation effect) in arid and semiarid regions. However, the importance of soil water and nutrient availability on shrub facilitation, and its trend along a drought gradient have been relatively less addressed in water-limited systems. We investigated species richness, plant size, soil total nitrogen and grass leaf δ13C within and outside the dominant leguminous cushion-like shrub Caragana versicolor along a water deficit gradient in drylands of Tibetan Plateau. We found that C. versicolor had a competitive or neutral effect on understory species richness at the paired-plot level. But increased community level species richness, as some species occur either under the shrub or in open areas. The effects of C. versicolor on understory plants were assessed species richness and plant size (RIIspecies and RIIsize, respectively) showed different trends along the water deficit gradient. RIIspecies showed a unimodal trend with decreasing water availability, while RIIsize did not significantly change. The effect of C. versicolor on soil nitrogen, rather than water availability, determines its overall effect on understory species richness. Neither the effect of C. versicolor on soil nitrogen nor water availability affected plant size. The shift of shrub facilitation on species richness at extreme dry site was related to the decreasing amelioration on soil nitrogen. Our study suggests that the drying tendency in association with the recent warming trends observed in drylands of Tibetan Plateau, will likely hinder the facilitation effect of nurse leguminous shrub on understories if moisture availability crosses a critical minimum threshold.